[PP.33.03] PREVALENCE AND CORRELATES OF NEW-ONSET LEFT VENTRICULAR GEOMETRIC ABNORMALITIES IN A GENERAL POPULATION: THE PAMELA STUDY. (September 2016) - Seravalle, G.; Cuspidi, C.; Facchetti, R.; Bombelli, M.; Brambilla, G.; Pizzala, D. Prata; Erba, G.; Dell'Oro, R.; Sala, C.; Tadjc, M.; Mancia, G.; Grassi, G.
Abstract : Objective: We sought to evaluate new-onset abnormal LV patterns and their correlates over a 10-year period in members of the general population enrolled in the PAMELA study. Design and method: The study included 817 subjects with normal LV geometry at baseline evaluation having a readable echocardiogram at the end of follow-up. Cut-points for abnormal LV geometric patterns were derived from reference values of the healthy fraction of the PAMELA population. Results: Over a 10-year period 39% of participants progressed to abnormal LV geometric patterns as follows: LV concentric remodelling (15.2 %), eccentric dilated LVH (8.4%), concentric LVH (7.9%), eccentric non-dilated LVH (6.8%), and concentric dilated LVH (0.7%). Age (OR: 1.051; 95% CI 1.037–1.066, p < 0.0001), LV mass index (OR : 1.039; 95% CI 1.026–1.052, p < 0.0001), night-time SBP (OR : 1.031; 95% CI 1.014–1.052, p = 0.0003) and BMI (OR : 1.082; 95% CI 1.032–1.135, p = 0.0001) emerged as key correlates of new-onset abnormal LV geometry. Age and LV mass index turned out to be strong determinants of all sub-types of LVH; whereas BP, BMI and sex exhibited a different predictive value across the various LV geometric patterns. Conclusions: Our study provides the first evidence that long-term changes from normal cardiac morphology towards to abnormal LV geometry represent a clinically relevant phenomenon at the community level. From a practical perspective this finding reinforces the concept that life-style changes and pharmacologic treatment aimed to reduce over-weight/obesity and optimize BP are of paramount importance for prevention of subclinical cardiac damage.